Adopting a pragmatic approach to the implementation of the music curriculum in colleges of education in Nigeria (2006)
Music, an important living art, features as a course of study more in colleges of education than any other tertiary institutions in Nigeria. Colleges of education are responsible for producing personnel who will teach at the primary and junior secondary school levels. However, there have been concerns from various quarters concerning the shortfalls of the music curriculum in these colleges especially with regard to its appropriateness within the local milieu. This study is an insider's appraisal of the music programme in these colleges, and it posits that the problem rests not so much with unsuitability of the music curriculum, but with its actual implementation. The problems associated with the implementation of the curriculum are discussed; these include inadequate staffing and funding as well as inadvertent misinterpretation of the content of the curriculum by some of the implementers. The paper identifies some practical ways whereby the state of musical arts education in the country could be improved and emphasizes the responsibilities of all stakeholders in ensuring that the music teachers of tomorrow could be better equipped to perform their expected roles.